Inclusion of Gaming Disorder in ICD has more advantages than disadvantages: Commentary on: Scholars’ open debate paper on the World Health Organization ICD-11 Gaming Disorder proposal (Aarseth et al.) - Király, Orsolya (J Behav Addict, 2017)
This paper is a response to a recent debate paper in which Aarseth et al. argue that the inclusion of a formal diagnosis and categories for problematic video gaming or Gaming Disorder (GD) in the World Health Organization’s 11th Revision of the International Classification of Diseases (ICD-11) is premature and therefore the proposal should be removed. The present authors systematically address all the six main arguments presented by Aarseth et al. and argue that, even though some of the concerns presented in the debate paper are legitimate, the inclusion of GD in ICD-11 has more advantages than disadvantages. Furthermore, the present authors also argue that the two GD subtypes (“GD, predominantly online” and “GD, predominantly offline”) are unnecessary and rather problematic; the main category for GD would be perfectly sufficient.